Generation of Orbital Angular Momentum Beam Using Fiber-to-Fiber Butt Coupling - Shuhui Li; Zhe Xu; Ruixuan Zhao; Li Shen; Cheng Du; Jian Wang (IEEE Photonics Journal)
We experimentally demonstrate a simple scheme for broadband generation of orbital angular momentum (OAM) using a fiber-based structure. A standard single-mode fiber (SMF) is stuck to a two-mode fiber (TMF) with specific offsets and tilt angles to realize high-order fiber mode conversion. By adjusting the polarization controllers implemented on the SMF and TWF accompanied with a polarizer filter, one can selectively obtain LP11 mode or OAM modes with l = ±1 at the output end of the TMF. We show the high-purity (extinction ratio >20 dB) generation of OAM modes within a wide range from 1480 to 1640 nm.